The morphology of fluvial‐tidal dunes: Lower Columbia River, Oregon/Washington, USA. Issue 8 (19th April 2022) - Prokocki, Eric W.; Best, James L.; Perillo, Maurico M.; Ashworth, Philip J.; Parsons, Daniel R.; Sambrook Smith, Gregory H.; Nicholas, Andrew P.; Simpson, Christopher J.
Abstract: This article quantifies changes in primary dune morphology of the mesotidal Lower Columbia River (LCR), USA, through ~90 river kilometres of its fluvial‐tidal transition at low‐river stage. Measurements were derived from a multibeam echo sounder dataset that captured bedform dimensions within the thalweg (≥ 9 m depth; H / H max ≥ 0.7) of the LCR main channel. Measurements revealed two categories of dunes: (i) fine to medium sand 'fluvial‐tidal to tidal' (upstream‐oriented, simple, and two‐dimensional) low‐angle dunes (heights ≈ 0.3–0.8 m; wavelengths ≈ 10–25 m; mean lee‐angles ≈ 7°–11°), and (ii) medium to coarse sand 'fluvial' (downstream‐oriented, compound, and 2.5‐dimensional to three‐dimensional) low‐angle dunes (heights ≈ 1.5–3 m; wavelengths ≈ 60–110 m; mean lee‐angles ≈ 11°–18°). At low‐river stage, where H / H max ≥ 0.7, approximately 86% of the fluvial‐tidal transition is populated by 'fluvial' dunes, whilst ~ 14% possesses 'fluvial‐tidal to tidal' dunes that form in the downstream‐most reaches. Thus, throughout the majority of the deepest channel segments of the fluvial‐tidal transition, seaward‐oriented river and ebb‐tidal currents govern dune morphology, whilst strong bidirectional tidal‐current influence is restricted to the downstream most reaches of the transition zone. Two mechanisms are reasoned to explain dune low‐angle character: (1) high‐suspended sediment transport near peak tidal‐currents that lowers the leeside‐angles of 'fluvial‐tidal to tidal' dunes, and (2) superimposed bedforms that erode the crests, leesides, and stoss‐sides, of 'fluvial' dunes, which results in the reduction of leeside‐angles. Fluctuations in river discharge create a 'dynamic morphology reach' at depths where H / H max ≥ 0.7, which spans river kilometres 12–40 and displays the greatest variation in dune morphology. Similar channel reaches likely exist in fluvial‐tidal transitions with analogous physical characteristics as the LCR and may provide a distinct signature for the fluvial‐tidal transition zone. Abstract : The primary dunes (≥ 9 m depth) within the fluvial‐tidal transition of the Lower Columbia River (LCR) mainly consist of seaward migrating low‐angle dunes (mean θ lee  ≤ 15°) that are 2.5‐ to 3‐dimensional, possess heights of ~1.5 to 3 m, wavelengths of 60 to 110 m, and are compound. Although bidirectional currents are present, these dunes are resemble fully‐fluvial dunes, which suggests that deep, primary dunes throughout fluvial‐tidal transitions with similar physical attributes to those of the LCR are likely governed by downstream‐currents.